Preliminary Validation of Linguistically and Culturally Adapted Social Exclusion Vignettes Based on the Social Information Processing Model in Indonesian Junior High School Students - Muflihatul Awalyah; Agny Nadya Yusniaulia; Karinta Elmira Amalia; Fitriani Yustikasari Lubis; Yanti Rubiyanti (IJIP : Indonesian Journal of Islamic Psychology, 2026)
Social exclusion is a common experience among adolescents and can influence how they interpret and respond to social situations. However, vignette-based instruments that capture adolescents’ cognitive processes in social exclusion contexts remain limited in Indonesia. This study aimed to conduct a preliminary linguistic and contextual adaptation of a Social Information Processing (SIP)-based social exclusion vignette for Indonesian adolescents. The adaptation process involved translation, expert review, cognitive interviews, and pilot testing. The findings suggest that the adapted vignettes are generally understandable and relevant to adolescents’ experiences, and that the structure is broadly consistent with the SIP framework. However, the results also revealed important psychometric limitations, particularly the low reliability of the hostile intent dimension and the limited stability associated with using only two items per factor. Therefore, the instrument should be considered a preliminary prototype rather than a validated tool and is not yet suitable for research or practical application without further development. Future studies are needed to refine the items, expand the number of indicators per dimension, and conduct confirmatory validation with larger samples.